2011
DOI: 10.1016/j.ijgo.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Female genital mutilation in Upper Egypt in the new millennium

Abstract: The incidence of FGM is still very high in Upper Egypt in spite of the criminalization law. While general practitioners perform most procedures, most nurses are in favor of preserving the practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 9 publications
4
59
1
Order By: Relevance
“…FGM is illegal in many countries of the world (Rahman & Toubia, 2000;Rasheed et al, 2011). However, the highly entrenched sense of social obligation overrides any potentially positively modifying influence of legal and moral norms, thereby fuelling the continuation of this practice (UNICEF, 2013).…”
mentioning
confidence: 99%
“…FGM is illegal in many countries of the world (Rahman & Toubia, 2000;Rasheed et al, 2011). However, the highly entrenched sense of social obligation overrides any potentially positively modifying influence of legal and moral norms, thereby fuelling the continuation of this practice (UNICEF, 2013).…”
mentioning
confidence: 99%
“…He reported that 72.3 of circumcised women complained of frigidity and 77.5 of circumcised women did not reach orgasm during coitus and they believed that circumcision is the cause for delayed orgasm [18]. Rasheed et al, reported that female circumcision led to delayed sexual arousal in 44% of circumcised women [19]. The difference between these studies may be explained by the fact that some women did not know the meaning of orgasm and the meaning of sexual pleasure differs from woman to woman.…”
Section: Discussionmentioning
confidence: 99%
“…[20], p. 186). Karmaker et al [21] and Rasheed et al [22] observed that within contexts where FGM is performed, the practice is not viewed as a dangerous procedure. Berg and Denison [23] pointed out that the general belief of health benefits of FGM is closely associated with hygiene and having clean genitalia as the female genitalia are seen as dirty and in need of being circumcised to become clean.…”
Section: Individual Levelmentioning
confidence: 99%
“…Residential area Another issue at the individual level, is the connection between FGM and the place of residency of a person. According to Rasheed et al [22], WHO (as cited in Ref. [19]), Cook (as cited in Ref.…”
Section: Individual Levelmentioning
confidence: 99%